Analysis Of Factors Affecting The Use Of Smartphone Digital Applications By Tourists In Yogyakarta When Traveling In The New Normal Period - Pramusita, Arina; Priyambodo, Tri Kuntoro; Mustofa, Khabib; Arymami, Dian (Al-Makki Publisher, 2023)
The Covid 19 Pandemic situation has had a significant impact on the tourism industry, that is decrease in a number of tourist activities and services due to the closure of a number of areas to prevent the spread of the virus. In this new normal period, adjustments for traveling are needed for tourists, that is the use of technology. This research aims to analyze the most influential factors in the use of digital smartphone applications as a form of adaptation to travel behavior in the new normal period. This research synthesizes TAM and TPB to provide a more comprehensive understanding of the behavior of using tourism digital applications during the pandemic. TAM explains factors related to perceived usefulness and ease of application use, while TPB provides a framework that involves psychological and social factors in explaining tourist intentions and behavior. This study uses a quantitative approach. Data collection was carried out using digital survey methods, interviews, and field observations. The data includes tourist profiles and tourist opinions. The sampling method is purposive sampling, with a sample size of around 160 respondents. The data is processed using Smart PLS. The results obtained from this research are (1) The synthesis between the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB) can provide a more comprehensive understanding of the behavior of using digital applications when traveling during the pandemic.